Vintage postcards from Old Spokane - Broyles, Duane (Tornado Creek Publications, 2005)
Locally owned Vintage Postcards and Stamps business provided many of the post card collections seen in this book. The authors both live in Spokane and love the history of the Spokane area. The postcards cover Spokane's history from the early days to the 1920s.